Analysis of the geometrical impact on the rubber damper properties - Ng, Soo Sien (2022)
Rail pad is a rubber damper used in the railway industry to lessen rail vibration and noise pollution caused by trains moving over the rail. The rail pad is placed between the rail and the sleepers, forming a soft interface between them that isolates vibration. The findings from many authors have demonstrated that the stiffness of rail pad is the critical parameter in determining the dynamic performance of rail track and should be given the utmost attention. Actual rail pads have certain geometrical features, such as studs and grooves, rather than being just a flat piece of rubber. However, there are no studies found in existing literature that are related to the impact of these geometrical features on the dynamic properies of rail pad. Moreover, other geometries can also be proposed on the rail pad, which also requires investigation onto its’ impact on rail pad’s dynamic properties. Hence, this study investigates the geometrical impact of normal, studded, grooved, holed, cut-out, and shaped rail pad designs onto their dynamic stiffness and energy dissipation by using simulation. In this study, ANSYS Transient Structural was used, and the Prony series material data for FC9 rail pad and dynamic loading conditions were referred from the literature as input for the simulation. From the simulation result, hysteresis loop was obtained and the dynamic properties were computed. The result of this study shows that the thickness is the only feature that can effectively increase dynamic stiffness and decrease energy dissipation, while other features or designs cannot. Moreover, thickness was found to be the most significant feature among all features discussed in this study, with dynamic stiffness improvement ratio (IR) range of 0.835 to 2.376 and energy dissipation IR range of 0.448 to 1.172. The second and third most significant features were also found to be the stud and cut-out features respectively. The dynamic stiffness and energy dissipation IRs for stud feature are in the range of 0.198 to 0.470 (stud diameter) and 1.734 to 3.443 (stud diameter) respectively. As for the cut-out feature, dynamic stiffness and energy dissipation IRs are in the range of 0.580 to 0.927 and 1.032 to 1.369 respectively. In addition, all the features discussed in this study except hole and shape causes a trade-off between dynamic stiffness and energy dissipation as the features are introduced.